Lebanon : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper analyzes the various transmission channels of the Syrian crisis-though quantification is hampered by the lack of reliable data-with focus on the impact on fiscal performance and labor markets; it also takes stock of international donor efforts to date. The paper also provides overviews of main effects on Lebanon's economy, the expenditure pressures associated with the refugee presence, the impact on poverty and inequality, and the added strains on labor markets. A section of the paper describes the response by the international community to help Lebanon cope with the Syrian crisis. Absent additional international support, the needs of both refugees and affected Lebanese communities will not be met. Sound government policies-including implementation of a concerted policy framework to deal with refugee issues and a commitment to fiscal discipline-will send credible signals to donors and help mobilize budget support. Tackling the unprecedented refugee crisis requires strong international support. There has been a large international humanitarian response, but much more is needed.